Bird Damage in Relation to Vertietal Differences in Bajra Crop - Jain, M B; Prakash, Ishwar (Annals of Arid Zone, 2016)
An indirect method of assessing damages to standing crop of Millet, Pennisetum typhoides, due to incidence of birds has been presented In the paper It was estimated that from maturity till harvest of the crop about 10 per cent of the bajra grains of the standing crop were lost due to birds. Hybrid bajra suffered more ( 144.03Â±2 .60 kg/ha ) losses as compared to RSK variety ( 80.20Â± 21.35 kg/ha ).